Local structure and evolution of phase transformation in Bi0.4871Na0.4871La0.0172TiO3–BaTiO3 materials - Atipong Bootchanont (2020)
© 2019 Elsevier Ltd and Techna Group S.r.l. Lead-free bismuth sodium lanthanum titanate and barium titanate (Bi0.4871Na0.4871La0.0172TiO3–BaTiO3; ((1-x)BNLT-xBT) ceramic system, where x = 0.00, 0.02, 0.04, 0.06, 0.08, and 0.10, were synthesized by a modified two-step mixed oxide method. The global structure was investigated by X-ray diffraction (XRD), while the local structure was elucidated by X-ray absorption near edge structure (XANES). The XRD results indicated a rhombohedral perovskite crystal structure for x < 0.04 and a tetragonal perovskite crystal structure for x ≥ 0.04. The Ti K-edge XANES spectra indicated a change in local structure around the Ti atom, which corresponds to an evolution of phase transition from rhombohedral to tetragonal structure in BNLT-BT system with increasing BaTiO3 content. A comparison between the measured and simulated spectra was obtained and discussed in details.